PENGOLAHAN JAJAN RUMPUT LAUT DI NUSA LEMBONGAN DALAM FOTOGRAFI STORY - I Putu Restu Dharayata; I Made Saryana; Anis Raharjo (Lp2mpp Isi Denpasar - Ps. Fotografi, 2023)
This research is a research based on This study aims to discuss seaweed which contains many nutrients and nutrients that can be beneficial for health when consumed, such as fiber, minerals, and vitamins. Not only delicious, consuming seaweed can provide health benefits. Seaweed can also be processed into vegetables, snacks, ice, and others. Lembongan water conditions are ideal for seaweed growth. Seaweed cultivation activities in Lembongan Village have been a prima donna that provide large income for business actors such as seaweed cultivators, processors and marketers. This is done through story photography and of course to add insight and knowledge of the community related to processed seaweed snacks. In addition, also to find out how to visualize seaweed snacks into story photography. The implementation method is carried out by digging data, analyzing data and presenting the results of data analysis. The process of extracting data can be reached through the methods of observation, interviews, participation and documentation. Several techniques that can be used to support the data mining method are recording, recording, and simulation. Most data presented in this study were translated in the form of images, charts, graphs and narratives. The results of this study produced 17 photo stories through visualization of images from the processing of biological resources, namely seaweed into processed snacks. Through this research, the wider community can have an option in disseminating promotional methods or other preparations of seaweed. By means of observation, interview and photo shoot Keywords: Processing, Seaweed, Story Photography, Nusa Lembongan